2005
DOI: 10.1002/pen.20448
|View full text |Cite
|
Sign up to set email alerts
|

Injection molding-induced morphology of thermoplastic polymer blends

Abstract: Various morphologies induced by injection molding are reviewed here. The structural hierarchy in the direction perpendicular to flow direction always appears in the injection-molded blends. The hierarchy involves three aspects: phase behavior hierarchy for the dispersed phase, crystalline or orientated structural hierarchy for the matrix, as well as hierarchy structure of co-continuous phase morphology. There are usually three layers in the injection-molded bars, i.e., the skin layer and the core region as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…This indicates that sample with a large number of finely dispersed domain could be achieved by injection molding. According to Zhong et al [15], smaller dispersed domain can be achieved due to large force acting on the dispersed domains induced by high injection flow rate causes the particles became more deformed and were easier to break up. Foaming behavior of PP/PS/PMMA (80/10/10) ternary blend system prepared by extruder and injection molding In our previous paper [6], we have reported that the pressure quench foaming result demonstrated an interesting phenomenon where a unique cell structure of PS/PMMA dispersed domain was kept their spherical shape and been encapsulated by large void space at foaming temperature range of 130 to 155 ºC.…”
Section: Results and Discussion Blend Morphology Characterizationmentioning
confidence: 99%
“…This indicates that sample with a large number of finely dispersed domain could be achieved by injection molding. According to Zhong et al [15], smaller dispersed domain can be achieved due to large force acting on the dispersed domains induced by high injection flow rate causes the particles became more deformed and were easier to break up. Foaming behavior of PP/PS/PMMA (80/10/10) ternary blend system prepared by extruder and injection molding In our previous paper [6], we have reported that the pressure quench foaming result demonstrated an interesting phenomenon where a unique cell structure of PS/PMMA dispersed domain was kept their spherical shape and been encapsulated by large void space at foaming temperature range of 130 to 155 ºC.…”
Section: Results and Discussion Blend Morphology Characterizationmentioning
confidence: 99%
“…4b). The presence of skin/core morphology in injection molded parts has been described for several immiscible blends [14][15][16]. In the PVC/PEHA blend, the PEHA dispersed domains at the rim are elliptically shaped (0.3-2 μm), while spherical PEHA particles (0.3-1 μm) appear in the core of the PVC/PEHA blend.…”
Section: Morphologymentioning
confidence: 97%
“…While many papers deal with the effect of polymer composition on the equilibrium morphology of high‐impact copolymers (i.e., as solidified from a quiescent melt), the consequences for the morphology and the related mechanical performance in injection‐moulded parts have been hardly studied. The limited number of publications dealing with morphological structures in injection‐molded or otherwise processed parts from PP/EPR model or reactor‐based systems are mostly restricted to one composition or one set of processing conditions . In contrast to this limitation, significant progress has been made in recent years in understanding the effect of composition variations, nucleation, and processing parameters on the crystal structure and the resulting mechanical performance of single‐phase PP homopolymers or random copolymers.…”
Section: Introductionmentioning
confidence: 99%